OUTCOME OF ALLOGENEIC STEM CELL TRANSPLANTATION FOLLOWING REDUCED-INTENSITY CONDITIONINIG REGIMEN IN PATIENTS WITH IDIOPATHIC MYELOFIBROSIS: THE G.I.T.M.O. EXPERIENCE AND REVIEW OF THE LITERATURE - Miriam Isola; Alessandra Sperotto; Andrea Bacigalupo; Francesca Patriarca; Maria Teresa Van Lint; Anna Paola Iori; Paolo Di Bartolomeo; Maurizio Musso; Pietro Pioltelli; Giuseppe Visani; Pasquale Iacopino; Renato Fanin; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background Allogeneic stem cell transplantation (SCT) is a potentially curative treatment for myelofibrosis (MI), though limited by a high rate of transplant-related mortality (TRM). . In the present study we evaluate the outcome of MI patients undergoing an allogeneic SCT after reduced intensity conditioning (RIC) regimens , and the impact of prognostic factors . Design and methods: Fifty two patients were transplanted in 26 Italian centres between 1998 and 2006. We analyzed the influence of patient and disease clinical features before SCT and of transplant procedures on TRM and overall survival (OS) by means of univariate and multivariate analyses. Results: At SCT, median age was 52,5 years (32-68) and 89% of the patients had an intermediate or high Dupriez score. Conditioning regimens were based on fludarabine plus busulphan in 27% of patients, thiotepa plus cyclophosphamide in 46% and miscellaneous drug combinations in the other 27% of cases. Stem cells came from matched sibling donors for 75% of the patients and mismatched sibling or unrelated donors for the remaining 25%. The cumulative incidence of engraftment at day 90 after transplant was 83% (95% CI, 0.87-0.97 ). The estimated 1-year TRM was 30%. The estimated 3- -year event-free-survival (EFS) and OS after hematopoietic SCT was 44% and 38% respectively. In multivariate analysis , an higher leukocyte count and circulating blasts in the peripheral blood before SCT significantly reduced EFS and OS respectively. Interpretation and conclusions: We conclude that the extension of the disease before transplantation based on the presence of circulating blasts and high leukocyte counts significantly affected the outcome after HSCT